Are We Ready for Whole Population Genomic Sequencing of Asymptomatic Newborns? - Vears DF; Savulescu J; Christodoulou J; Wall M; Newson AJ (Dove Medical Press, 2023)
Danya F Vears,1,2 Julian Savulescu,3- 6 John Christodoulou,1,2 Meaghan Wall,7 Ainsley J Newson8 1Murdoch Children's Research Institute, The Royal Children's Hospital, Parkville, Victoria, Australia; 2University of Melbourne, Melbourne, Victoria, 3052, Australia; 3Chen Su Lan Centennial Professor in Medical Ethics, Centre for Biomedical Ethics, Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 4Visiting Professorial Fellow in Biomedical Ethics, Murdoch Children's Research Institute, Parkville, Victoria, Australia; 5Distinguished Visiting Professor in Law, Melbourne University, Carlton, Victoria, Australia; 6Oxford Uehiro Centre for Practical Ethics, University of Oxford, Oxford, UK; 7Victorian Clinical Genetics Service, Murdoch Children's Research Institute, Parkville, Victoria, Australia; 8Faculty of Medicine & Health, Sydney School of Public Health, Sydney Health Ethics, The University of Sydney, Sydney, New South Wales, AustraliaCorrespondence: Danya F Vears, Biomedical Ethics Research Group, Murdoch Children's Research Institute, Parkville, Victoria, 3052, Australia, Email danya.vears@mcri.edu.auAbstract: The introduction of genomic sequencing technologies into routine newborn screening programs in some form is not only inevitable but also already occurring in some settings. The question is therefore not "if" but "when and how" genomic newborn screening (GNBS) should be implemented. In April 2022, the Centre for Ethics of Paediatric Genomics held a one-day symposium exploring ethical issues relating to the use of genomic sequencing in a range of clinical settings. This review article synthesises the panel discussion and presents both the potential benefits of wide-scale implementation of genomic newborn screening, as well as its practical and ethical issues, including obtaining appropriate consent, and health system implications. A more in-depth understanding of the barriers associated with implementing genomic newborn screening is critical to the success of GNBS programs, both from a practical perspective and also in order to maintain public trust in an important public health initiative.Keywords: bioethics, infants, consent, genomic sequencing